What We Have Known About and Will Learn From COVID-19 | Dr. Stephen Morse - Ren, Renee (2020)
In this episode of WiGH?, JGH Online co-Chair Renee Ren speaks with Dr. Stephen Morse on how viral infections originate and spread, how preventative policies control epidemics, vaccines, and the 2019 coronavirus epidemic. Dr. Morse is the Professor of Ep